Enhancing innovation speed through trust: A case study on reframing employee defensive routines - Christina Marie Mitcheltree (Journal of Innovation and Entrepreneurship, 2021)
Trust in organizations plays an essential role for efficient innovation implementation. However, trust between managers and employees is under-communicated in relation to innovation speed. Innovation speed is related to innovation adoption, concerning new ways of performing laboratory services within the health sector. The purpose of this case study is to investigate how trust mechanisms may enhance innovation speed by reducing employee decisions to perform defensive routines. The focus is related to trust as a social condition for enhancing innovation acceptance in the context of management and organizing styles subject to the Norwegian Work Life Model.
Keywords: 650; Case study; Defensive routines; Health care; Innovation adoption; Innovation speed; Organizational innovation; Trust